2023
DOI: 10.51620/0869-2084-2022-67-10-561-569
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Blood Biomarkers in the Prospective Follow-Up of Patients With Cardiovascular Pathology in Combination With Type 2 Diabetes Mellitus After Covid-19 Associated Pneumonia

Abstract: The study of the characteristics and dynamics of laboratory biomarkers in patients with cardiovascular diseases (CVD) with type 2 diabetes mellitus who underwent COVID-19-associated pneumonia is of great clinical importance for preventing the risk of adverse events. IN the study we used data from 65 patients in the present work. Patients were divided into 2 groups: group 1 included patients with CVD: arterial hypertension (AH) in combination with coronary artery disease (CAD) without DM2 (n=45), group 2 includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 46 , 47 NLR, MLR, PLR and SII have also been proposed as biomarkers to assess the severity, morbidity, mortality and prognosis of psychiatric and non-psychiatric illnesses. 48 Likewise, it has been reported that NLR and other inflammatory markers decrease after a few weeks compared to acute COVID-19 levels 49 , 50 Although SII, NLR and PLR are suggested to predict the risk of severe COVID-19 and mortality, the inflammatory indices could decrease over time in COVID-19 survivors. 30 , 49 , 51 According to this, individuals with post-COVID condition have shown a relationship between the severity of deterioration and age, where younger patients show impairment in some cognitive domain more frequently than older ones.…”
Section: Discussionmentioning
confidence: 99%
“… 46 , 47 NLR, MLR, PLR and SII have also been proposed as biomarkers to assess the severity, morbidity, mortality and prognosis of psychiatric and non-psychiatric illnesses. 48 Likewise, it has been reported that NLR and other inflammatory markers decrease after a few weeks compared to acute COVID-19 levels 49 , 50 Although SII, NLR and PLR are suggested to predict the risk of severe COVID-19 and mortality, the inflammatory indices could decrease over time in COVID-19 survivors. 30 , 49 , 51 According to this, individuals with post-COVID condition have shown a relationship between the severity of deterioration and age, where younger patients show impairment in some cognitive domain more frequently than older ones.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection predisposes individuals to hypercoagulation and thrombotic complications, often leading to poor prognosis and necessitating intensive care regardless of the presence of diabetes ( Abdi et al, 2022 ; Abou-Ismail et al, 2020 ; Abrignani et al, 2022 ; Desdiani, 2022 ). In addition, COVID-19 patients with pre-existing diabetes are more likely to develop severe or critical thromboembolic complications relative to those without diabetes ( Petelina et al, 2022 ; Tang et al, 2020 ). However, the relationship between diabetes and SARS-CoV-2 infection-related symptoms, underlying pathogenic mechanisms in COVID-19 patients with diabetes, and effective treatment strategies have not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%